Historical museum collections clarify the evolutionary history of cryptic species radiation in the world's largest amphibians. Issue 18 (16th September 2019) - Turvey, Samuel T.; Marr, Melissa M.; Barnes, Ian; Brace, Selina; Tapley, Benjamin; Murphy, Robert W.; Zhao, Ermi; Cunningham, Andrew A.
Abstract: Inaccurate taxonomic assessment of threatened populations can hinder conservation prioritization and management, with human‐mediated population movements obscuring biogeographic patterns and confounding reconstructions of evolutionary history. Giant salamanders were formerly distributed widely across China, and are interpreted as a single species, Andrias davidianus . Previous phylogenetic studies have identified distinct Chinese giant salamander lineages but were unable to associate these consistently with different landscapes, probably because population structure has been modified by human‐mediated translocations for recent commercial farming. We investigated the evolutionary history and relationships of allopatric Chinese giant salamander populations with Next‐Generation Sequencing methods, using historical museum specimens and late 20th‐century samples, and retrieved partial or near‐complete mitogenomes for 17 individuals. Samples from populations unlikely to have been affected by translocations form three clades from separate regions of China, spatially congruent with isolation by either major river drainages or mountain ranges. Pliocene–Pleistocene divergences for these clades are consistent with topographic modification of southern China associated with uplift of the Qinghai‐Tibet Plateau. General Mixed Yule Coalescent model analysis indicates that these clades represent separate species: Andrias davidianus (Blanchard, 1871) (northern Yangtze/Sichuan), Andrias sligoi (Boulenger, 1924) (Pearl/Nanling), and an undescribed species (Huangshan). Andrias sligoi is possibly the world's largest amphibian. Inclusion of additional reportedly wild samples from areas of known giant salamander exploitation and movement leads to increasing loss of biogeographic signal. Wild Chinese giant salamander populations are now critically depleted or extirpated, and conservation actions should be updated to recognize the existence of multiple species. Abstract : Giant salamanders were formerly distributed widely across China, and are interpreted as a single species, Andrias davidianus . We investigated the evolutionary history and relationships of allopatric Chinese giant salamander populations with Next‐Generation Sequencing methods, using historical museum specimens and late 20th century samples, and retrieved partial or near‐complete mitogenomes for 17 individuals. Samples cluster within three clades from separate regions of China, and represent three separate species, of which Andrias sligoi rather than Andrias davidianus is possibly the world's largest amphibian.